Morality, ethics and responsibility in organization and management - McMurray, Robert, 1972-; Linstead, Alison, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"In the aftermath of the financial crisis, and regular corporate scandals, there has been a growing concern with the moral and ethical foundations of business. Often these concerns are limited to narrow accounts of governance codes, regulatory procedures or behaviour incentives, which are often characterized by neo-liberal bias underpinned by western masculine logics. This book challenges these limited accounts of ethics and responsibility. It looks at the writing of Gayatri C. Spivak who takes globally networked markets, people, and ideas and provides tools to rethink subjectivity, ethics, and corporate governance. Eschewing strict hierarchical notions of authority and identity, Spivak's work invites us to consider who speaks for whom and for what in organizational contexts. Relationality is also to be found in the radical politics and feminist ethics of Judith Butler who continues to draw on and develop her account of performativity to interpret contemporary organizations, management and work. While popular accounts of corporate ethics often concern themselves with the aims and actions of those at the top of organisations, Lauren Berlant focuses on the struggles of those at the bottom of the new social structures created by contemporary forms of capital. Finally, the book also considers ecological challenges through the work of Val Plumwood, who spent a lifetime considering the threats and responsibilities we face in environmental terms, and developed a feminist ecological philosophy for understanding social and species differences. This book will be relevant to students and researchers across business and management, organizational studies, critical management studies, gender studies and sociology"--
OCLC-licensed vendor bibliographic record.
Keywords: Business ethics; Social responsibility of business; Management -- Moral and ethical aspects; Organizational sociology; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Organizational Behavior